PENGARUH GETARAN TERHADAP KERUSAKAN MEKANIS TOMAT (Lycopersicum esculentum Mill) - Zelzha Arinnesia Varanita; Tamrin -; Agus Haryanto (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2016)
Mechanical damage that occurs in tomatoes only visible and probably most who do not know. Without realizingit experienced mechanical damage tomato fruit will make the tomatoes are not worth selling because the fruit isdamaged. This research aims to determine how much damage suffered mechanical damage tomatoes mechanicalvibrated at different times. Varieties of tomatoes used are tomato gondol at the age of 70-80 days of harvest. Inthis research, tomatoes put in a storage container as much as 3 squares and vibrated at different times. As manyas 20% of tomatoes which can not be used in the research because of a pest when planting and rub with a storagecontainer (pallet). The results showed that the tomatoes will suffer mechanical damage such as bruises, scars andwounds ruptured (perforated top). The length of time the magnitude of vibration could be the benchmark ofmechanical damage to the fruit. However, it must also show the hardness of tomatoes to be vibrated. Tomatoessuffered mechanical damage until the worst was bruised and perforated top so that the fruit is not worth selling.Mechanical damage which is obtained not only from research through visual or tangible, but found to be anumber. The highest value of weight loss is on T3L2 with a value of 2,07% by weight of the intensity valueshrinkage of 1,66%. Percentage of tomatoes are not worth selling at 6,79% due to the damage caused by theprovision of mechanical vibration, with wide intensity mechanical damage amounting to 3,08%.Keywords: Tomato (Lycopersicum esculentum Mill), mechanical damage, respiratory and climacteric.